2012
DOI: 10.1007/s00586-012-2222-2
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar spinal stenosis treatment with aperius perclid interspinous system

Abstract: PurposeThe purpose of this study is to report clinical outcome and imaging changes of percutaneous Aperius stand-alone implant in patients with degenerative lumbar spinal stenosis and neurogenic intermittent claudication, which did not respond to conservative treatment.MethodBetween January 2008 and July 2010, 37 patients (20 males and 17 females) with mean age of 64.3 years underwent surgery for the onset of claudicatio spinalis with Aperius PercLID interspinous device (Medtronic). In all patients, the diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
3
10
0
Order By: Relevance
“…Another study reported durable reductions in VAS score and quality-of-life measures to 12 months (16); similar reductions in VAS and ODI scores were reported in a smaller retrospectively studied cohort of 37 patients at mean 18-month follow-up (17). Our study adds to the existing literature by providing data for durable reduction in VAS and ODI scores in a cohort of Note-Data are presented as number (%) or mean Ϯ SD.…”
Section: Discussionsupporting
confidence: 85%
“…Another study reported durable reductions in VAS score and quality-of-life measures to 12 months (16); similar reductions in VAS and ODI scores were reported in a smaller retrospectively studied cohort of 37 patients at mean 18-month follow-up (17). Our study adds to the existing literature by providing data for durable reduction in VAS and ODI scores in a cohort of Note-Data are presented as number (%) or mean Ϯ SD.…”
Section: Discussionsupporting
confidence: 85%
“…If clinical examination is uncertain, a magnetic resonance imaging should be obtained and minimally invasive procedures could eventually be performed. 19 Moreover, the study from Naziri et al reported excellent survival rates in a similar to the present population, but Carli et al described some concern for early Tritanium cup loosening. Our survivorship rate was comparably excellent and up to now the alarm for early mobilization of the cup cannot be seen: the only prematurely loose cup was due to its primary undersizing that probably never achieved optimal fixation and osseointegration.…”
Section: Discussionsupporting
confidence: 62%
“…Postoperatively, IPDs have shown good short-time clinical effects, but the long-term results have been less clear and a high reoperation rate compared to ODS has been reported [9][10][11]. In contradiction to the lack of long-term improvement in subjective symptoms and high reoperation rates, some studies have shown beneficial radiological effects [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Not many studies have been published on the radiological effects of IPDs, either by conventional MRI or with the spine in a loaded position, such as upright MRI or axial loading during MRI (alMRI). A few studies have reported a small but statistically significant increase regarding the dural sac and spinal canal cross-sectional area after IPD insertion [12,15,16], even up to 2 years postoperatively. However, these studies all lack a control group and do not provide any information regarding the effect on adjacent levels.…”
Section: Introductionmentioning
confidence: 99%